Diagnostic and Therapeutic Challenges of Rare Urogenital Cancers: Urothelial Carcinoma of the Renal Pelvis, Ureters and Urethra - Cassell, Ayun (World J Oncol, 2021)
Urothelial carcinoma (UC) is a neoplastic growth that affects the lining of the urinary tract from the renal pelvis to the distal urethra. Urothelial cancer occurs less commonly along the upper urinary tract (renal pelvis and ureter) accounting for 5-10% and even rarer along the urethra approximately less than 1%. The incidence of UC of the upper urinary tract and urethra has been reported in the United States and Europe by the Surveillance, Epidemiology, and End Results Program and the Rare Cancers in Europe project, respectively. Considering the rarity of upper tract urothelial carcinoma (UTUC) and primary urethral cancer (PUC), there is a paucity of data from Sub-Saharan Africa. Both the European Association of Urology guideline and the National Comprehensive Cancer Network guideline have provided some clinical updates on the management of UTUC and PUC. However, UTUC and PUC present mostly at a more advanced stage than UC of bladder. A high index of suspicion is necessary for diagnosis even more for UTUC. Organ-sparing surgery is possible for both localized UTUC and PUC but stringent follow-up with urine cytology, endoscopy and imaging is mandated for early detection of recurrence.